Pengembangan Media Pop-Up Book Berbasis Qr Code Bangun Ruang pada Kelas V UPTD SDN Keleyan 1 Socah - Zainul Umam; Dya Qurotul A’yun (Mataram University, 2026)
This study aims to develop a QR Code-based Pop-Up Book media for spatial geometry material for fifth-grade students at UPTD SDN Keleyan 1 Socah that meets the criteria of validity, effectiveness, and engagement. This study is a Research and Development (R&D) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of three validators: a media expert, a material expert, and an instructional design expert, as well as 21 fifth-grade students at UPTD SDN Keleyan 1 Socah. Data collection techniques used interviews, questionnaires, observations, and tests. Data analysis was carried out quantitatively by calculating the percentage of expert validation results, observations of teacher and student activities, learning test results, and teacher and student questionnaire responses. The results showed that the QR Code-based Pop-Up Book media achieved a validity level of 93.33% from media experts, 87.5% from material experts, and 98.1% from instructional design experts, with a very valid category. The effectiveness of the media is shown through observations of teacher activity of 99.22% and student activity of 88.64%, with the active category. The results of the learning test show that students have achieved learning mastery in accordance with the Learning Objectives Achievement Criteria (KKTP). The attractiveness of the media is shown by the results of the teacher response questionnaire of 97.5% and student responses of 96.66%, with the very interesting category. Based on these results, the QR Code-based Pop-Up Book media is declared suitable for use as a mathematics learning medium for spatial geometry in fifth grade elementary school because it meets the criteria of validity, effectiveness, and attractiveness.